Flax and hemp nonwoven composites: The contribution of interfacial bonding to improving tensile properties - Merotte, Justin; Le Duigou, Antoine; Kervoelen, Antoine; Bourmaud, Alain; Behlouli, Karim; Sire, Olivier; Baley, Christophe (Polymer testing, 2018)
The purpose of this article is to understand the influence of typical composite parameters (interfacial bond strength, surface-area and fibre mechanical properties) on the tensile properties of nonwoven composite materials. The materials investigated were flax, hemp and Poly-(propylene) (PP) and Maleic Anhydride-grafted PP (MAPP), which provide different configurations in terms of fibre mechanical properties, bundle individualization and fibre/matrix interface. Whereas hemp fibres exhibit poorer tensile properties and lower bundle individualization than flax fibres, their higher lignin content evaluated by FT-IR analysis improves the interfacial shear strength (IFSS) with PP and MAPP. However, the tight interface developed with hemp fibres has only a weak effect at the scale of composites. With low-IFSS systems such as plant fibres associated with polyolefin matrices, mechanical properties at the macroscale are governed by the fibre mechanical properties and bonding area rather than by the interfacial bond strength. •Multiscale evaluation of the tensile properties of natural fibre nonwoven composite materials.•Hemp fibres exhibit lower tensile properties and bundle individualization than flax fibres but higher interfacial shear strength (IFSS).•At the composite scale, flax composites show better mechanical properties.•Mechanical properties at the macroscale are governed by the fibre mechanical properties and bonding area.